mnhoff

13 Reputation

7 Badges

9 years, 189 days

MaplePrimes Activity


These are questions asked by mnhoff

Hi I have the expressions: I1 := M*[1-a*exp(-i*theta)]/(1-b*cos(theta)) I2 := M*[1-a*i*exp(i*theta)]/(1+b*sin(theta)) I3 := M*[1+a*exp(-i*theta)]/(1+b*cos(theta)) I4 := M*[1+a*i*exp(i*theta)]/(1-b*sin(theta)) x1 := M*[1-a*cos(theta)]/(1-b*cos(theta)) x2 := M*[1+a*sin(theta)]/(1+b*sin(theta)) x3 := M*[1+a*cos(theta)]/(1+b*cos(theta)) x4 := M*[1-a*sin(theta)]/(1-b*sin(theta)) y1 := M*a*i*sin(theta)/(1-b*cos(theta)) y2 := M*a*i*cos(theta)/(1+b*sin(theta)) y3 := -M*a*i*sin(theta)/(1+b*cos(theta)) y4 := -M*a*i*cos(theta)/(1-b*sin(theta)) I enter the following expression
1 2 Page 2 of 2